Novel 1, 1-dimethyl-3-phenyl-3-(5-phenyl-1, 3, 4- thiadiazol-2-yl) urea derivative has potential antiproliferative activity against human leukemia cell lines - K562 - Ahirwar, Khemkaran; Jain, Sanmati K.; Tamrakar, Bholenath (Journal of Applied Pharmaceutical Research, 2014)
Cancer is thought to be caused by the interaction between genetic susceptibility and environmental toxins. Based on the DNA changes in cells, proliferating cycle of tumor cells can be divided into 4 phases. Pre-synthetic phase (Gap 1 phase or G1 phase). Cells chiefly make preparations for the synthesis of DNA. Synthetic phase (S phase). Cells are synthesizing their DNA. Post-synthetic phase (Gap 2 phases or G2 phase). DNA duplication has been finished and they are equally divided to the two of future sub-cells. Mitosis phase (M Phase). Each cell is divided into two sub-cells. Some of these new cells enter the new proliferating cycle, the others become non-proliferating cells. G0 phase cells have proliferation ability but do not divide temporally. When proliferating cells are suffered heavy casualties, G0 phase cells will get into proliferating cycle and become the reasons of tumor recurrence.G0 phase cells are usually not sensitive to antineoplastic drugs, which is the important obstacle to tumor.chemotherapy. The antiproliferative activities of these compounds wee evaluated against a Cytotoxicity analysis of compounds against leukemia cell line -K562 organism homo sapiens(human) organ bone â marrow, tissue - lymphoblast, disease â chronic myelogenous leukemia(CML) one human tumor cell lines(K562) by applying the MTT colorimetric assay. The 1, 3-disubstituted urea derivatives show good antiproliferative activity against human cancer cell lines (K562). The hydroxyl groups on the phenyl ring reduced the antiproliferative activities.